Ethics-Driven Digital Learning Governance in the Civil Service - Herlina, Besse; Syamsiar, Syamsiar; Mustaking, Mustaking (Jurnal Manajemen Pelayanan Publik, 2025)
This study investigated the impact of civil servants’ bureaucratic ethics, encompassing integrity, accountability, and transparency, on the effectiveness of digital learning governance within the context of digital transformation in the public sector. This study also explored the role of civil servants’ digital capacity, internal policies, and information and communication technology (ICT) infrastructure as moderation variables in these relationships. The research methodology applied a qualitative approach; data were collected through surveys from civil servants involved in digital learning programs. The results of statistical analysis demonstrated that civil servants’ bureaucratic ethics have a significant positive influence on the effectiveness of digital learning governance. Furthermore, the digital capacity of civil servants and ICT infrastructure significantly strengthens the relationship, while internal policies show a more limited influence of moderation. These findings confirm that the application of solid bureaucratic ethical values, supported by adequate digital resources and policies, is the key to the successful implementation of effective digital learning governance. The practical implications of this study are essential for strengthening the integrity, accountability, and transparency of civil servants as well as increasing digital capacity to support the development of adaptive human resources in the digital era.